Association between skeletal muscle mass and serum concentrations of lipoprotein lipase, GPIHBP1, and hepatic triglyceride lipase in young Japanese men - Matsumoto, Ryutaro (Lipids Health Dis, 2019)
BACKGROUND: Two important regulators for circulating lipid metabolisms are lipoprotein lipase (LPL) and hepatic triglyceride lipase (HTGL). In relation to this, glycosylphosphatidylinositol anchored high-density lipoprotein binding protein 1 (GPIHBP1) has been shown to have a vital role in LPL lipolytic processing. However, the relationships between skeletal muscle mass and lipid metabolism, including LPL, GPIHBP1, and HTGL, remain to be elucidated. Demonstration of these relationships may lead to clarification of the metabolic dysfunctions caused by sarcopenia. In this study, these relationships were investigated in young Japanese men who had no age-related factors; participants included wrestling athletes with abundant skeletal muscle. METHODS: A total of 111 young Japanese men who were not taking medications were enrolled; 70 wrestling athletes and 41 control students were included. The participants’ body compositions, serum concentrations of lipoprotein, LPL, GPIHBP1 and HTGL and thyroid function test results were determined under conditions of no extreme dietary restrictions and exercises. RESULTS: Compared with the control participants, wrestling athletes had significantly higher skeletal muscle index (SMI) (p < 0.001), higher serum concentrations of LPL (p < 0.001) and GPIHBP1 (p < 0.001), and lower fat mass index (p = 0.024). Kruskal–Wallis tests with Bonferroni multiple comparison tests showed that serum LPL and GPIHBP1 concentrations were significantly higher in the participants with higher SMI. Spearman’s correlation analyses showed that SMI was positively correlated with LPL (ρ = 0.341, p < 0.001) and GPIHBP1 (ρ = 0.309, p = 0.001) concentration. The serum concentrations of LPL and GPIHBP1 were also inversely correlated with serum concentrations of triglyceride (LPL, ρ = − 0.198, p = 0.037; GPIHBP1, ρ = − 0.249, p = 0.008). Serum HTGL concentration was positively correlated with serum concentrations of total cholesterol (ρ = 0.308, p = 0.001), low-density lipoprotein-cholesterol (ρ = 0.336, p < 0.001), and free 3,5,3′-triiodothyronine (ρ = 0.260, p = 0.006), but not with SMI. CONCLUSIONS: The results suggest that increased skeletal muscle mass leads to improvements in energy metabolism by promoting triglyceride-rich lipoprotein hydrolysis through the increase in circulating LPL and GPIHBP1.